2006
DOI: 10.1002/ejlt.200600157
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids

Abstract: EndocannabinoidsThe endocannabinoid system embraces a group of lipid molecules, enzymes and receptor proteins. This system appears to be involved in the modulation of neurotransmitter release thereby modifying learning and memory, in the regulation of food intake, and in the modulation of inflammation and pain and several other physiological/ pathophysiological conditions. Furthermore, naturally occurring structural analogues of one of the endocannabinoids also appear to have beneficial biological activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 194 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…Several possible mechanisms for this action have been suggested including inhibition of phospholipase D (PLDalpha) [15], interaction with phytohormone signaling pathways [16], and modulation of ABI3 transcript levels [17]. However, NAEs have multiple targets in animal systems and perturbation of NAE levels is known to affect a broad range of processes in animals [18]. It is likely that NAE metabolism interacts with several different targets in plant systems, including inhibition of LOX enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Several possible mechanisms for this action have been suggested including inhibition of phospholipase D (PLDalpha) [15], interaction with phytohormone signaling pathways [16], and modulation of ABI3 transcript levels [17]. However, NAEs have multiple targets in animal systems and perturbation of NAE levels is known to affect a broad range of processes in animals [18]. It is likely that NAE metabolism interacts with several different targets in plant systems, including inhibition of LOX enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The endocannabinoid system is a complex signalling system comprised of lipid molecules, enzymes and G-protein coupled receptors responsible for mediating a wide range of effects in organisms such as modifying neurotransmitter release, modulating learning and memory, regulating food intake and modulating inflammation and pain reception [313]. These effects are mediated through the activation of cannabinoid receptor 1 (CB1) and cannabinoid receptor 2 (CB2), the latter of which is primarily expressed in the cells of the immune system, including microglia [314,315].…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Within the past decade, arachidonoylethanolamide (AEA, also called anandamide) and 2‐arachidonoylglycerol (2‐AG) (Fig. 1) have been demonstrated to be agonists for the two known cannabinoid receptors, the CB 1 receptor and the CB 2 receptor (14–16), which are involved in such diverse functions as regulation of food intake, neurotransmitter release, bone formation and pain (17–20). Recently, it has been reported that AEA and 2‐AG also can activate the orphan receptor GPR55 but the biological significance is at present unknown (21).…”
Section: Endocannabinoids Are Derivatives Of Arachidonic Acidmentioning
confidence: 99%